Desmoplastic melanoma: The role of pure and mixed subtype in sentinel lymph node biopsy and survival - Annelien E. Laeijendecker; Mary‐Ann El Sharouni; Vigfús Sigurdsson; Paul J. vanDiest (Cancer Medicine, 2020)
Abstract Background Desmoplastic melanoma (DM) is an uncommon type of melanoma. Two histological subtypes of DM can be distinguished: pure and mixed (PDM and MDM). We hypothesized that discrimination between these subtypes is associated with sentinel lymph node biopsy (SLNB) status and survival. Methods Clinicopathological data from PALGA, the Dutch Pathology Register were retrieved from patients diagnosed with DM in The Netherlands between 2000 and 2014. Clinical and pathological variables were extracted from pathology text files, including pure or mixed desmoplastic morphology. A Cox proportional hazard model was performed for overall and recurrence‐free survival (OS and RFS). Results A total of 239 patients with DM were included, representing 0.4% of all primary cutaneous melanoma in The Netherlands. A total of 114 PDM and 125 MDM patients were identified. MDM was significantly associated with positive SLNB status (P = .035). In multivariable analysis, age (HR 1.10, 95% CI 1.07‐1.14, P < .001) and ulceration (HR 1.98, 95% CI 1.05‐3.75, P = .036) were significant predictors for OS. For RFS, mixed subtype (HR 2.72 95% CI 1.07‐6.89, P = .035), male gender (HR 2.54, 95% CI 1.03‐6.27, P = .043), and Breslow thickness (HR 1.13 per mm, 95% CI 1.05‐1.21, P = .001) were significant predictors. Conclusion MDM is significantly associated with a positive SLNB status. Mixed subtype is significantly correlated with RFS, but not with OS. The distinction between pure and mixed desmoplastic subtype therefore seems to be of clinical importance.